2012
DOI: 10.1111/j.1475-6773.2012.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Chronic Care Management for Heart Failure: Meta‐Regression Analyses to Explain the Heterogeneity in Outcomes

Abstract: Objective. To support decision making on how to best redesign chronic care by studying the heterogeneity in effectiveness across chronic care management evaluations for heart failure. Data Sources. Reviews and primary studies that evaluated chronic care management interventions. Study Design. A systematic review including meta-regression analyses to investigate three potential sources of heterogeneity in effectiveness: study quality, length of followup, and number of chronic care model components. Principal Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 82 publications
1
83
0
5
Order By: Relevance
“…The usefulness and relevance of existing assessment instruments are limited as several of the quality assessment criteria are not applicable to studies on comprehensive care [89]. Also the Health Technology Assessment-Disease Management (HTA-DM) instrument [89] which was specifically developed to assess the quality of complex interventions such as comprehensive care has limitations and needs further validation [28,90]. We therefore decided to select six criteria from existing quality criteria lists [35,36] that in our opinion were most relevant for the assessment of studies on comprehensive care programs.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness and relevance of existing assessment instruments are limited as several of the quality assessment criteria are not applicable to studies on comprehensive care [89]. Also the Health Technology Assessment-Disease Management (HTA-DM) instrument [89] which was specifically developed to assess the quality of complex interventions such as comprehensive care has limitations and needs further validation [28,90]. We therefore decided to select six criteria from existing quality criteria lists [35,36] that in our opinion were most relevant for the assessment of studies on comprehensive care programs.…”
Section: Discussionmentioning
confidence: 99%
“…La supervivencia en pacientes con IC no solo se ha visto asociada con los tratamientos, sino que también tienen un importante peso atribuible en la supervivencia factores organizativos como la coordinación entre niveles, la planificación del seguimiento, la educación a los pacientes y su monitorización continua 31 . El objetivo del manejo de la IC debe ser reducir el riesgo de ingresos hospitalarios, lo que va a mejorar la calidad de vida y reducirá los costes de la atención a estos pacientes.…”
Section: Discussionunclassified
“…5 Chronic illness management (CIM), a care model which emphasizes continuity of care and promotes self-management support for patients, could therefore provide an opportunity to improve long-term outcomes post HTx given promising results in other chronic patient populations. 5,8,9 Studies in non-HTx populations have shown that CIM is associated with decreased healthcare utilization, 10,11 improvements in health-related behaviors, 12 increased quality-of-life, 11 and greater patient and caregiver satisfaction. 12 In transplantation, the reengineering of transplant follow-up care according to the principles of CIM has resulted in improved clinical outcomes, reduced health care utilization, and reduced costs.…”
Section: Introductionmentioning
confidence: 99%